Analisis Model Keputusan Dengan Metode TOPSIS untuk Menilai Kualitas Air Minum Isi Ulang - Sinaga, Mikha Dayan; Hardiyanti, Yeni; Sembiring, Nita; Haryanto, Edy Victor; Nababan, Labuan; Sianturi, Charles Jhony Mantho (CSRID (Computer Science Research and Its Development Journal), 2025)
Water is one of the basic needs for every living thing, including humans. About three-quarters of our body consists of water and no one can survive more than 4-5 days without drinking water. Drinking water with clean quality is very important for the human body, because if the water drunk is not clean water, it will cause various diseases in the human body. Quality drinking water is very important for water depot businesses as one of the attractions in product marketing, if wrong in determining the quality of water, it will have an impact on decreasing marketing and sales of the business, so that business profits are not optimal. The problem that many drinking water depot business actors face today is the difficulty of determining suppliers of quality drinking water providers based on detection of drinking water quality so that the water produced is in accordance with health standards. The TOPSIS method (Technique for Order of Preference by Similarity to Ideal Solution) is one of the decision-making techniques that can be used to evaluate various alternatives based on predetermined criteria. The results of the study showed significant variations in the quality of refill drinking water among the samples tested. Based on the calculation using the TOPSIS method, Supplier A obtained the highest ranking with a preference score of 0.61493219, while Supplier 5 had the lowest ranking with a score of 0.16023232. This study emphasizes the importance of selecting a quality water provider and the need for stricter supervision from the government. The results of the study are expected to provide useful information for consumers and refill drinking water providers, as well as become a basis for further research in the field of water quality.